Aquagenic acrokeratoderma in a 5-year-old boy. - Zhang, R.; Zhu, W.; Yu, Y. (European Journal of Pediatric Dermatology, 2009)
Aquagenic acrokeratoderma is a rare acquired condition characterized by papules and translucent plaques with prominent eccrine ducts that develop after a 2- to 4-minute exposure to water. We present a new case contributing to the knowledge of this disease, which is underdiagnosed thus far in our opinion, given the clinical presentation of the lesions.